Clean air policy challenges in Europe: achieving air standards that prevent disease - Stauffer, A (Eur J Public Health, 2020)
Despite a large regulatory framework on clean air, air pollution in the European Union continues to be the top environmental threat to health, leading to approx. 400,000 early deaths annually and high health costs. Over 20 of the 27 EU countries fail to keep air quality standards, which for key pollutants are already less strict than what the World Health Organization (WHO) recommends. In the EU Green Deal Communication, the European Commission has pledged to align current standards more closely with WHO. At the same time, the latest science underlines that there is no safe level of air pollution, and WHO is reviewing current guidelines. In EU neighbouring countries, the need to act on clean air standards is even more pressing. During the COVID-19 lockdown, many countries have witness a drop in air pollution, especially in cities. As transport and economic activities kick in again, pollution is on the rebound, making the need for long-term clean air even more apparent. The presentation/paper will showcase ongoing policy opportunities at EU and national level, and discuss how the health sector can become engaged to prevent chronic disease from poor air quality, especially as part of a healthy, green and just recovery.